2015
DOI: 10.1007/s00251-014-0825-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the spleen transcriptome in domestic turkey (Meleagris gallopavo) in response to aflatoxin B1 and probiotics

Abstract: Poultry are highly susceptible to the immunotoxic effects of the food-borne mycotoxin aflatoxin B1 (AFB1). Exposure impairs cell-mediated and humoral immunity, limits vaccine efficacy, and increases the incidence of costly secondary infections. We investigated the molecular mechanisms of AFB1 immunotoxicity and the ability of a Lactobacillus-based probiotic to protect against aflatoxicosis in the domestic turkey (Meleagris gallopavo). The spleen transcriptome was examined by RNA sequencing (RNA-seq) of 12 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 86 publications
(104 reference statements)
0
34
0
Order By: Relevance
“…Similar to expression changes in other species, transcriptome analysis in the turkey found that more genes were up-regulated than down-regulated by AFB1 [227,238,240]. In one study of the liver, more than 80 genes belonging to cancer or focal adhesion pathways were up-regulated during aflatoxicosis, whereas smaller numbers of genes involved in cell signaling, cytoskeleton, and cell cycle were also up-regulated [227].…”
Section: Poultry Transcriptomics and Afb1mentioning
confidence: 94%
See 2 more Smart Citations
“…Similar to expression changes in other species, transcriptome analysis in the turkey found that more genes were up-regulated than down-regulated by AFB1 [227,238,240]. In one study of the liver, more than 80 genes belonging to cancer or focal adhesion pathways were up-regulated during aflatoxicosis, whereas smaller numbers of genes involved in cell signaling, cytoskeleton, and cell cycle were also up-regulated [227].…”
Section: Poultry Transcriptomics and Afb1mentioning
confidence: 94%
“…Although some genes are well characterized, the functions and expression patterns of many poultry MHC genes are still unknown. In the turkey, expression of multiple MHC genes significantly increased in response to AFB1 exposure [238].…”
Section: Cytokines and The Mhcmentioning
confidence: 98%
See 1 more Smart Citation
“…Investigating the results of changes in liver enzymes gene expression indicated that increase in gene expression related to interleukins, liver enzymes and especially enzymes involved in the metabolism of aflatoxin occurs under the influence of aflatoxin [28] . It seems that changes in gene expression levels in the liver occurs by using aflatoxin contaminated diets therefore acute and chronic aflatoxicosis occur due to the liver proliferation 2 [12] . Studies on the impact of diets contaminated with aflatoxin on gene expression in liver enzymes showed that the presence of toxin in the diet causes to upregulation of CYP450 1A gene.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitations of aluminosilicate consumption, using biological compounds is on the agenda of nutritionists because of their numerous advantages. It has been proved that using diets based on the probiotic compounds especially Lactobacilli in poultry diets, have the ability to reduce aflatoxin effects on the gene expression of liver enzymes such as genes for amino acids and fat metabolizing enzymes [12] . Gao et al [13] found the high ability of Bacillus Subtilis for reducing the effects or disable B 1 , M 1 and G 1 aflatoxins.…”
Section: Introductionmentioning
confidence: 99%